Descriptive study of the utility of individual tracking tool in program monitoring for prevention of mother-to-child transmission of HIV, Maharashtra, India. Issue 1 (March 2016) - Gupta, R.S.; Hegde, Asha; Mulik, Tejas; Yewale, Kiran; Babu, P.K. Amarnath; Pardeshi, Kushalsinh; Balkrishnan, Sudha; Seguy, Nicole; Reddy, D.C.S.
Abstract : Objective: The objective is to describe the utility of prevention of parent-to-child transmission tracking tool in terms of the in-depth information that it provides for better decision making to improve the services. Methods: The excel-based tracking tool is initiated by 578 Integrated Counselling and Testing Centre (ICTC) Counsellor and shared with 70 antiretroviral treatment (ART) centres. Between April and September 2014, total of 1118 HIV-infected pregnant women were registered in the tool. The secondary data for this period that is captured in the prevention of parent-to-child transmission tracking tool has been analyzed and presented in this descriptive study. Results: Of the total 1118 HIV-positive pregnant women, registered in the tool, 760 (68%) were newly detected with HIV infection and 358 (32%) had already been detected before their current pregnancy. In total, 1095 (98%) pregnant women were registered at ART centre out of which 1007 (91%) were initiated on lifelong ART. The average time delay between HIV detection and registration at ART centre was 12 days ( n = 844). In this cohort of 1118 pregnant women, 45% delivered live babies, 7% underwent medical termination of pregnancy, 2% were stillbirths and abortions, and 46% were yet to deliver. Only 29 infants were tested for HIV at 6 weeks of age and six were found reactive. Conclusion: The tracking tool provides in-depth information regarding the pregnant women registered in the program and in the tracking tool. The information throws more light on the characteristics of the registered women and the various services provided to them and highlight key areas where the program has to be improved. The tool is effective for assessing the treatment status of HIV-positive pregnant woman, retention in care and early infant diagnosis of the baby. The tool has identified programmatic bottlenecks component wise such as the need to focus on earlier detection of HIV-positive women during pregnancy, decreasing the time delay between detection and ART registration, and improving the early infant diagnosis.